2007
DOI: 10.1038/sj.bjc.6603590
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of 5-fluorouracil refractory metastatic colorectal cancer: an Australian population-based analysis

Abstract: Randomised trials have established the importance of oxaliplatin (O) and irinotecan (I) in advanced colorectal cancer (CRC). However, patients enrolled in clinical studies represent a restricted population and little is known about the use of O and I in the general population and the subsequent outcomes outside clinical studies. We used the Australian Health Insurance Commission (HIC) database to describe prescribing patterns of O and I and their impact on survival in all patients with 5-fluorouracil (5-FU) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…30 However, the most recent PBS statistics highlight the growth, particularly in relation to PBS spend, on specialist-initiated medicines such as antineoplastics (cancer drugs). We have very limited research in this important and growing area of therapeutics [31][32][33][34] given cancer represents a significant disease burden in the Australian population. 30 Moreover, populations such as the elderly, children, pregnant women and those with multiple morbidities are studied rarely in pre-market evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, the most recent PBS statistics highlight the growth, particularly in relation to PBS spend, on specialist-initiated medicines such as antineoplastics (cancer drugs). We have very limited research in this important and growing area of therapeutics [31][32][33][34] given cancer represents a significant disease burden in the Australian population. 30 Moreover, populations such as the elderly, children, pregnant women and those with multiple morbidities are studied rarely in pre-market evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings included changing trends over time and variation in rates of treatment by patient demographic and health characteristics (ie, age, gender, socioeconomic status, tumor stage, metastatic tumor status, presence of comorbidities), hospital setting and volume, and region (26,(28)(29)(30)34,(36)(37)(38)40,42,45,(46)(47)(48)55,60,61,66,68,69,72,78,79,88). Among these characteristics, patient age was one of the most consistent findings associated with treatment receipt, with older patients being less likely to receive colorectal cancer care compared with younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also indicated that younger patients were more likely to receive chemotherapy compared with older patients, though some highlighted rising rates of chemotherapy use among the elderly over time (28)(29)(30)40,46,47,60,61,66,68,69,78,79). Additionally, more advanced tumor stage greatly increased the likelihood of chemotherapy receipt (30,40,49,50,54,61,(63)(64)(65)(66)68,73,78,79).…”
Section: Initial Treatmentmentioning
confidence: 99%
“…These signs are especially useful in chronic disease populations where one would expect regular medical interactions, including the dispensing of prescribed medications. The death proxy approach has been demonstrated recently by Damianovich et al . who estimated 6‐ and 12‐month survival in Australian metastatic colorectal cancer patients prescribed oxaliplatin and irinotecan under the national Pharmaceutical Benefits Scheme (PBS).…”
Section: Introductionmentioning
confidence: 99%
“…These signs are especially useful in chronic disease populations where one would expect regular medical interactions, including the dispensing of prescribed medications. The death proxy approach has been demonstrated recently by Damianovich et al 3 who estimated 6-and 12-month survival in Australian metastatic colorectal cancer patients prescribed oxaliplatin and irinotecan under the national Pharmaceutical Benefits Scheme (PBS). At the time of the study, death data were not routinely collected by Medicare Australia, the PBS administering body, so the investigators classified patients as dead if they had no dispensing records for any drug after 6 and 12 months from entry into the study, respectively.…”
Section: Introductionmentioning
confidence: 99%